PENERAPAN MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING TERHADAP MINAT BELAJAR SISWA DENGAN MATERI USAHA DAN ENERGI - Apsari, Nurul; Irawan, Pingki; Lestari, Novika (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2025)
This study aims to determine how students' learning interests are after implementing the guided discovery learning model. This type of research is a qualitative descriptive study with a population of class X and a sample size of 29 students. Data collection techniques were carried out using non-tests with research instruments being questionnaires, observations and interviews. The data analysis technique used was descriptive analysis. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. Checking the validity of the data in this study was carried out using technical triangulation. The results showed that students were very interested in all indicators of interest (attention, feelings of pleasure, interest, involvement) using the Guided Discovery Learning model on the material of work and energy.